Axiological Aspect of the Novel by N. Musin “There are the Remains of a Batyr” (Proceedings of Southern Federal University. Philology, 2021)
Gulnur M. Nabiullina (Ufa, Russian Federation)A comprehensive study of the historical novel by the Bashkir prose writer Nuguman Musin revealed the axiological aspect of the work. The author uses the motifs of the folklore heritage, introducing truly folk features into his work, developing the traditions of national artistic prose, enriching it with new spiritual content based on the Islamic religion. The compositional center of the novel is the image of Aldar Batyr, who embodies the strength of the heroic spirit of the people, inherited from their ancestors. The religiosity of the characters determines their humane attitude to nature, where the forest is designated as a spiritual principle and consolidates moral forces, thus, nature becomes the most important object of testing a person for morality, performing the role of «spiritual substance». Religious relations in the novel are transformed and acquire a new artistic function, opening up the possibility of a long-term vision of the traditions of Islam in an axiological perspective.Key words: historical novel, Aldar Batyr, religious approach, moral attitude, Bashkir forest, object of testing.DOI 10.18522/1995-0640-2021-2-156-165